Kant's definition of an intellectual in the Age of Enlightenment - Radovanović, Saša Ž (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
The paper discusses Kant's definition of a scientist as an intellectual in the Age of Enlightenment. The relationship between reason and mind as set forth in the Critique of the Pure Mind is analyzed. The analysis is complemented by considering the difference between public and private uses of the mind. The problem of freedom is also interpreted within this difference. The public use of mind as a scholarly position is linked to three basic requirements for thinking: thinking independently, thinking for another, and thinking consistently. These three requirements are determined as necessary conditions in the formation of intellectual engagement. At the end of the paper, it is concluded that Kant's essay on enlightenment simultaneously places Kant in the position of a scientist and an intellectual.
Keywords: enlightenment; thinking; understanding; reason; intellectual; Immanuel Kant